Should We Treat Ventilator-Associated Tracheobronchitis with Antibiotics? - Martin-Loeches, Ignacio; Coakley, John Davies; Nseir, Saad (Seminars in Respiratory and Critical Care Medicine, 2017)
Patients admitted to intensive care units (ICUs) often require lung organ support. The use of mechanical ventilation, while lifesaving can be associated with subsequent complications. The most common complication in patients under mechanical ventilation is the development of ventilator-associated lower respiratory tract infections (VA-LRTIs). Before the development of VA-LRTI, there is a continuum process that ranges from airway colonization to ventilator-associated pneumonia (VAP). There is an intermediate process called ventilator-associated tracheobronchitis (VAT). Contemporary treatment of VA-LRTI emphasizes the importance of prompt broad-spectrum antimicrobial therapy. Previous studies reported prolonged duration of mechanical ventilation and ICU stay in patients with VAT. This negative impact on outcome is related to increased inflammation of the lower respiratory tract, sputum production, and higher rates of VAP. Extubation failure and difficult weaning have been reported to be associated with increased sputum volume in mechanically ventilated patients. Antibiotic treatment for VAT patients is still a matter for debate. Observational studies suggested a beneficial effect of antimicrobial treatment in VAT patients, including a reduced duration of mechanical ventilation and lower rates of subsequent VAP. Previous studies demonstrated beneficial effects of systemic and aerosolized antibiotics in preventing VAP in critically ill patients. However, antibiotic treatment is a recognized risk factor for the emergence of multidrug-resistant bacteria. Infections related to these bacteria are associated with increased morbidity, mortality, and cost. Therefore, a large well-designed study is warranted to determine whether patients with VAT should receive antimicrobials. Furthermore, a short course of antimicrobials could be sufficient in these patients.
Keywords: sepsis; intensive care; ventilator-associated tracheobronchitis; pneumonia; antimicrobial